2017
DOI: 10.1016/j.drugalcdep.2016.12.016
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary longitudinal study of white matter alteration in cocaine use disorder subjects

Abstract: Background Previous diffusion tensor imaging (DTI) studies have consistently shown that subjects with cocaine use disorder (CocUD) had altered white matter microstructure in the corpus callosum. It is believed that these alterations are due to preexisting factors, chronic cocaine use, or both. However, there is no published longitudinal DTI study on human cocaine users yet which could shed light on the relationship between cocaine use and DTI findings. Methods This study used a longitudinal design and DTI to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 51 publications
(79 reference statements)
3
34
0
Order By: Relevance
“…Similarly, they found that lifetime cocaine use negatively predicts callosal FA. Together, these studies provide fairly consistent evidence that cocaine abuse negatively impacts white matter microstructure (Ma et al, 2017). Finally, white matter FA also seems to track treatment outcome, with higher FA significantly predicting the number of successful days of abstinence from cocaine (Bell, Foxe, Nierenberg, Hoptman, & Garavan, 2011;Xu et al, 2010).…”
Section: Causality and Trackingmentioning
confidence: 54%
“…Similarly, they found that lifetime cocaine use negatively predicts callosal FA. Together, these studies provide fairly consistent evidence that cocaine abuse negatively impacts white matter microstructure (Ma et al, 2017). Finally, white matter FA also seems to track treatment outcome, with higher FA significantly predicting the number of successful days of abstinence from cocaine (Bell, Foxe, Nierenberg, Hoptman, & Garavan, 2011;Xu et al, 2010).…”
Section: Causality and Trackingmentioning
confidence: 54%
“…As several previous studies have revealed that the disease status at proximally located/neighbouring voxels can be similar (see Wu et al, 2013;Xue, Bowman & Kang, 2018), our method is expected to be more clinically meaningful than other studies given that the detected regions are spatially contiguous. Furthermore, our test is able to detect additional regions of differences compared to clinical cocaine dependence studies that rely on FA summaries, such as Ma et al (2017), which did not find these regions despite using the same dataset. The MCMC trace plots and posterior densities of the Potts spatial dependence parameters are displayed in Figure 10.…”
Section: Application: Cocaine Dependence Studymentioning
confidence: 87%
“…We now use our Potts model to analyze the dataset concerning cocaine users (Ma et al, 2017), which we previously described in Section 2. The data were provided by the Institute for Drug and Alcohol Studies, Virginia Commonwealth University.…”
Section: Application: Cocaine Dependence Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Cocaine use disorder (CUD) patients exhibit altered white matter integrity versus non-drug using controls [1][2][3][4][5][6][7], with the most consistent findings in the corpus callosum. The altered white matter integrity is particularly evident in CUD patients with greater severity of cocaine use [4].…”
Section: Introductionmentioning
confidence: 99%